Optimalisasi Pendistribusian Dana Zakat, Infak, Shadaqah Pada Masa Pandemi Covid-19 di Baznas Kabupaten Ponorogo - Dita Lestari; Moch. Khoirul Anwar (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
This research aims to find out the distribution of Zakat, Infak, and Shadaqah (ZIS) funds in the Baznas Ponorogo Regency during the pandemic and to find out whether the distribution has been optimal or not. The study uses a descriptive qualitative and a phenomenological approach. Based on the analysis of the final data generated, there was a procedure for filing requests, assessment of the eligibility the candidates of mustahik, and determination and submission of ZIS funds during the pandemic. The distribution activities in the Baznas Ponorogo Regency have been appropriate and optimal according to UU Nomor 23 Tahun 2011, Fatwa MUI Nomor 23 Tahun 2020 and SE Nomor 8 Tahun 2020.